Special and gifted education (Vol.2): concepts, methodologies, tools, and applications - Information Resources Management Association, Ed (IGI Global, 2016)
"This exhaustive compilation of emerging research, theoretical concepts, and real-world examples of the ways in which the education of special needs and exceptional children is evolving emphasizes pedagogical innovation and new ways of looking at contemporary educational practice"--